2020
DOI: 10.11648/j.ijde.20200504.14
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Electrolytes Including Calcium and Magnesium Imbalance with Etiology Assessment in Patients Admitted in Endocrine Department of a Tertiary Care Hospital

Abstract: Objectives: Several endocrine disorders have marked effects on fluid, electrolyte, and acid-base homeostasis including diabetic ketoacidosis, hyperglycemic hyperosmolar state, and acute adrenal crisis etc. An understanding of the etiology behind the development of these electrolytes along with calcium and magnesium imbalance helps to guide therapy and improves the clinical outcome. The aim of this study to see the pattern of electrolytes, calcium and magnesium imbalance with etiology assessment in patients adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In a single center study, the prevalence of Conn syndrome was reported to be 2.6% of patients in primary care [3]. Patients with CS may account for as many as half of the patients admitted to the endocrinology department due to hypokalemia [4]. Primary hyperaldosteronism (PHa) appears to be the most common endocrine cause of secondary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In a single center study, the prevalence of Conn syndrome was reported to be 2.6% of patients in primary care [3]. Patients with CS may account for as many as half of the patients admitted to the endocrinology department due to hypokalemia [4]. Primary hyperaldosteronism (PHa) appears to be the most common endocrine cause of secondary hypertension.…”
Section: Discussionmentioning
confidence: 99%